TRANSFORMASI ADMINISTRASI PERKANTORAN MELALUI INTEGRASI ARTIFICIAL INTELLIGENCE STRATEGI OPTIMALISASI EFISIENSI DAN PRODUKTIVITAS DI ERA DIGITAL - Hedian Dena Fritiar, Inkha (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2025)
The development of Artifical Intelligence (AI) technology has had a significant impact across various fields, including office administration. The integration of AI in the digital era is a strategic step to enhance efficiency and productivity. This study employs a secondary literature analysis method, sourcing information from research jurnals and related articles. The research findings reveal that AI integration provides effective strategies for achieving higher efficiency and productivity. For instance, in document management, the use of AI improves the accuracy of data retrieval. OCR technology and text analysis enable automated archiving and document search processes, reducing manual workloads. In communication, the use of chatbots and virtual asisstants increases employee satisfaction and speeds up response time, as AI delivers quick and accurate answers. Additionally, in decision making AI reduces human errors, supporting more precise and efficient decisions. However there are still challenges in the process, such as employees not fully understanding how to use new technology, necessitating further training and learning. Moreover there are obstacles in implementing AI including implementation cost, employee acceptance, and ethical issues related to the use of AI. Keywords: productivity, digital, office administration, artificial intelligence, automation, efficiency